Indian Public Sector Banks in the Widening Horizon: A Study Vis-A-Vis their Performance Indicators - Hugar, S. S.; Vaz, Nancy H. (Indian Journal of Finance, 2009)
Survival in the context of global competition calls for acceptable performance by the Indian Banks. Bank performance is gauged by evaluating financial performance indicators pertaining to their soundness and profitability. While opening of the Indian economy to global Banks, a question to ask would be: How strong and financially viable are the Indian Banks, especially those in the Public Sector, to stand to the ensuing competition? Indian economy has just woken up to a competitive scene after a stupor of almost fifty years where it was leaning more towards a socialistic pattern. This question is important in the light of the fact that Indian Public Sector Banks form the backbone of the economy.